Excited leptonic states in polarized e(-)gamma and e(+)e(-) collisions - Eboli, OJP; Gregores, E. M.; Montero, J. C.; Novaes, Sérgio Ferraz [UNESP]; Spehler, D. (American Physical Soc, 1996)
We analyze the capability of the next generation of Linear electron-positron colliders to unravel the spin and couplings of excited leptons predicted by composite models. Assuming that these machines will be able to operate both in the e(+)e(-) and e(-)gamma modes, we study the effects of the excited electrons of spin 1/2 and 3/2 in the reactions e(-)gamma --> e(-)gamma and e(+)e(-) --> gamma gamma. We show how the use of polarized beams is able not only to increase the reach of these machines, but also to determine the spin and couplings of the excited states.